Optical and magnetic properties of Ba-doped CdS thin films. (2nd November 2017) - Samiyammal, P.; Parasuraman, K.; Prabha, D.; Usharani, K.; Balu, A. R.
ABSTRACT: Spray technique using perfume atomiser is used to deposit Ba-doped CdS (CdS:Ba) thin films on glass substrates. Barium concentration is varied as 0, 1, 2 and 3 wt-% and the effect of Ba doping level on some physical properties of the CdS films is reported in this paper. XRD studies confirm that the undoped and doped films exhibit hexagonal crystal structure with a strong (0 0 2) preferential orientation. Nanosized rod shaped grains are evinced for the heavily doped films. The mapping images confirm the distribution of the host ions Cd, S and the dopant ion Ba on the film surface. Increased transparency is observed for the doped films. Magnetic studies confirm that the doped films exhibit ferromagnetic behaviour. The obtained results confirm that barium, a cationic dopant ion enhances the optical and magnetic properties of CdS thin films to a large extent.